A systematic review and meta-analysis of the prevalence of Listeria monocytogenes in South-East Asia; a one-health approach of human-animal-food-environment - Jibo, Garba Gidandawa; Raji, Yakubu Egigogo; Salawudeen, Adamu; Amin-Nordin, Syafinaz; Mansor, Rozaihan; Tengku Jamaluddin, Tengku Zetty Maztura (Elsevier, 2022)
Listeria monocytogenes is an important foodborne intracellular pathogen. The pathogen is the primary cause of human Listeriosis. The main source of human Listeriosis is through consumption of contaminated food products. Other modes of transmission include zoonotic and vertical transmission. The disease often presents in a mild form, but severe and fatal cases, as well as outbreaks, may occur. Despite these challenges, there has been little attempt at enumerating the burden of the disease in countries of Southeast Asia (SEA) and some developing countries. Thus, this study investigated the prevalence of L. monocytogenes in SEA using one health approach through a systematic review and meta-analysis (SR&MA) of the existing literature. In accordance with the PRISMA guidelines, an a priori protocol for the SR&MA was developed and registered in PROSPERO (ID=CRD42021288903). A systematic search of four electronic databases was performed for relevant citations. The identified publications were screened, and 17 studies were included in the review from where data was extracted. The pooling of the prevalence estimate (with the 95% confidence interval [CI]) was done using the random effect model by employing the double transformed arcsine method using MetaXL software. The overall determined prevalence for L. monocytogenes in SEA (in food, animal, and environmental sources) was 16% (95% confidence interval [CI]: 10–23). Further subgroup analysis revealed ready-to-eat food of vegetable origin with the highest prevalence of 21% (CI: 6–41). Also, seven virulence genes were identified to be prevalent in the subregion. The commonest identification method was found to be the polymerase chain reaction (PCR). The knowledge of the high prevalence of L. monocytogenes in SEA is relevant for informed decision making by clinicians, public health practitioners, and policymakers. To achieve the goal of the effective control and prevention of the disease in the subregion.